KEGIATAN PENGELOLAAN SAMPAH DAN PENGHIJAUAN OLEH DASA WISMA AZALEA RT 3 RW 16 DESA MANGLIAWAN KECAMATAN PAKIS KABUPATEN MALANG - Susilo Bekti; Ardian Anjar Pangestuti; Enis Fitriani (JPM PAMBUDI, 2019)
The Environmental Office OF Malang Regency (DLH) noted that the amount of waste produced by the people of Malang Regency reached 1004.58 tons/day and as many as 273.33 tons/day waste could not be utilized. Dasa Wisma Azalea is one of the environmental activist community in RT 03 RW 16 Mangliawan Village, Pakis Subistrict, Malang Regency. The thought from the members of Dasa Wisma Azalea stated that the members of community took part in increasing the amount of waste generation in Malang Regency. Based on this thought Dasa Wisma Azalea carried out efforts to manage waste generated by the members of community and plant a variety of useful plants. The programs carried out by Dasa Wisma Azalea include conducting comparative study activity, procuring inorganic storage areas, procuring composter barrels, sorting organic and inorganic waste, making organic fertilizer, sorting inorganic waste, utilizing inorganic waste, buying family medicinal plants (TOGA), vegetables, fruit-producing plants and ornamental plants, as well as maintaining and harvesting the plants. These activity program worked well, this was proven by the RT 03 environment got the 3rd rank in the environmental competition in August 2018 whereas in the previous year RT 03 got the 7th rank.